1987
DOI: 10.1095/biolreprod37.5.1129
|View full text |Cite
|
Sign up to set email alerts
|

Inositol Phosphates Accumulation in Ovarian Granulosa After Stimulation by Luteinizing Hormone1

Abstract: Accumulation of inositol phosphates by granulosa cells from medium follicles of porcine ovaries was studied to determine if hydrolysis of phosphoinositides is stimulated by luteinizing hormone (LH). Although follicle-stimulating hormone (FSH), D-alanine-gonadotropin-releasing hormone (D-ala-GnRH), and dibutyryl cyclic adenosine 3',5'-monophosphate (dbcAMP) had no effect, LH increased accumulation of inositol phosphate (IP), -bisphosphate (IP2), and trisphosphate (IP3) by severalfold. Furthermore, 0.01 microgra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…The present study demonstrates that carbachol stimulates inositol phosphate synthesis in hen granulosa cells with a time dependency similar to that seen in previous studies on granulosa cells [20,21] and other cell types [22]. This is also consistent with recent studies in a variety of cell types demonstrating that some, but not all, muscarinic receptor subtypes are coupled to inositol phospholipid-specific phospholipase C (PLC) (see [23]).…”
Section: Discussionsupporting
confidence: 91%
“…The present study demonstrates that carbachol stimulates inositol phosphate synthesis in hen granulosa cells with a time dependency similar to that seen in previous studies on granulosa cells [20,21] and other cell types [22]. This is also consistent with recent studies in a variety of cell types demonstrating that some, but not all, muscarinic receptor subtypes are coupled to inositol phospholipid-specific phospholipase C (PLC) (see [23]).…”
Section: Discussionsupporting
confidence: 91%
“…LH has been shown to increase IP turnover in bovine and porcine luteal and granulosa cells, respectively (Davis et al, 1987;Dimino et al, 1987); and in the present study this is demonstrated to be true for the hamster as well. EGF, however, did not affect total IP levels except for a small increase at 60 min.…”
Section: Discussionsupporting
confidence: 72%
“…In the mammalian ovary, it is well known that FSH and LH elicit their steroidogenic effects, at least partially, through the protein kinase A (PKA) pathway [1,2]. LH also elicits its steroidogenic effects through activation of the PKC/Ca 2 + pathway [3,4] as evidenced by the dual coupling of recombinant LH receptors to both signaling pathways [5]. In contrast, FSH does not appear to stimulate steroidogenesis through activation of the protein kinase C (PKC)/Ca 2 + pathway [4,6], despite its ability to elevate intracellular Ca 2+ concentrations in granulosa cells [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…LH also elicits its steroidogenic effects through activation of the PKC/Ca 2 + pathway [3,4] as evidenced by the dual coupling of recombinant LH receptors to both signaling pathways [5]. In contrast, FSH does not appear to stimulate steroidogenesis through activation of the protein kinase C (PKC)/Ca 2 + pathway [4,6], despite its ability to elevate intracellular Ca 2+ concentrations in granulosa cells [7,8]. Therefore, it appears that FSH and LH may stimulate the production of ovarian ster- oids through different combinations of intracellular signaling pathways.…”
Section: Introductionmentioning
confidence: 99%